THE APPLICATION OF PROJECT BASED LEARNING IN IMPROVING THE STUDENTS OF TWELFTH GRADERS ACHIEVEMENT ON SPEAKING AND WRITING SKILLS OF PUBLIC VOCATIONAL HIGH SCHOOL 3 KAYUAGUNG - Okta Rizki (Universitas PGRI Palembang, 2013)
ABSTRACTThis study aimed to investigate the effects of application of Project-based learning (PBL) on writing and speaking skills or oral presentation to the twelve graders of Public Vocational High School (Sekolah Menengah Kejuruan Negeri or SMKN) 3 Kayuagung and also to know about the students’ perception on the application of PBL. This study involved 60 students as the sample (PBL group 30 students and Non-PBL group 30 students). The sample students were given pre and post test. The data were obtained by average scores of test andquestionnaires as the instruments and achieve documents. The scoring were done by two raters. The topic which choose was ‘manual book”, with the final products were a procedure text and oral presentation of the topic was choose.The result shows that there was a slight improvement in the average score between the pre and post-test of writing product and oral presentation between Non-PBL and PBL group. In post-test writing product of Non-PBL group the average score was 13.07 or 65.35% students were in mastery level, while in PBL group was 14.82 or 74.10% students were in mastery level. And for oral presentation in Non-PBL group was 12.77 or 63.85% students were in mastery level, while in PBL group was 14.05 or 70.25% students were in mastery level. The finding in the questionnaire shows that the twelve graders perception on the use of project-based learning shown that 28 of 30 responders or 93.88% students were interested and full of fun with the PBL in class, 20 responders or 66.66% students choose that the most interesting activity in PBL was using information technology, and 21 responders or 71.00% students choose that the most uninteresting and dislike activity in PBL was assessing way.Keywords : project-based learning, achievement, writing and speaking skills.